KREATIVITAS ANAK USIA DINI DALAM PEMANFAATAN LIMBAH ECENG GONDOK KELOMPOK B DI TK NEGERI PEMBINA KOTA BARAT KOTA GORONTALO - Niluh Ria Karmini; Rapi Us. Djuko; Nunung Suryana Jamin (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2021)
This study aims to develop children’s creativity in the utilization of group B water hyacinth waste at the Negeri Pembina Kindergarten, Kota Gorontalo, Gorontalo City. The number of children involved as a sample is 24 people who were selected by purposive sampling. This study uses a qualitative approach and data collection techniques with interviews, observation, and documentation. The results show that the development of children’s creativity in the use of water hyacinth waste is classified as good, especially in the three indicators observed, namely (1) originality, (2) fluency, (3) flexibility. The results of this study are expected to add insight to parents and teachers in developing activities to improve children’s creativity.